2007
DOI: 10.1177/0003319707305246
|View full text |Cite
|
Sign up to set email alerts
|

Malondialdehyde as an Indicator of Oxidative Stress During Abdominal Aortic Aneurysm Repair

Abstract: Ischemia-reperfusion injury significantly contributes to abdominal aortic aneurysm (AAA)- related mortality and morbidity; therefore, we measured oxidative stress during open AAA repair and investigated any potential associations with intraoperative or perioperative events (aortic clamping time, blood loss, and the need to transfer to the intensive care unit). Blood samples were collected at specific time points from 53 patients undergoing open AAA repair: (1) before induction of anesthesia; (2) 15, 30, 60, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…21 Among them, blood levels of malondialdehyde were significantly increased in AAA patients. 22 Likewise, we have measured MPO in plasma of AAA patients, a wellrecognized oxidative stress biomarker of different cardiovascular pathologies, 23,24 showing that MPO plasma levels are increased not only in large AAA, 7 but also in small AAA. In the other hand, catalase plasma levels were significantly decreased in small and large AAA patients relative to control subjects.…”
Section: Discussionmentioning
confidence: 98%
“…21 Among them, blood levels of malondialdehyde were significantly increased in AAA patients. 22 Likewise, we have measured MPO in plasma of AAA patients, a wellrecognized oxidative stress biomarker of different cardiovascular pathologies, 23,24 showing that MPO plasma levels are increased not only in large AAA, 7 but also in small AAA. In the other hand, catalase plasma levels were significantly decreased in small and large AAA patients relative to control subjects.…”
Section: Discussionmentioning
confidence: 98%
“…In a previous study, lower TAS levels were found to be related to lower perioperative complications (11). Papalambros et al found MDA levels to be higher in patients with long lengths of stay in intensive care after elective or urgent AAA (2).…”
Section: Discussionmentioning
confidence: 99%
“…Being a less invasive procedure, less intense OS may contribute to EVAR's lower mortality and morbidity rates. IRI in OR not only results in local damage but also in distant organ injury (2,7,14). In AAA patients, it is reported that OS is correlated with myocardial infarction and lung damage (3,11,15,16).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main effect of I/R is the activation of inflammatory pathways with oxidative stress occurring during aortic clamping and subsequent reperfusion [7]. The synthesis of cytokines during the inflammatory processes generates an increase in concentrations of acute-phase proteins as a response to tissue destruction [8], while high-grade oxidative stress during AAA repair operation has been related with a complicated postoperative course and transfer to intensive care unit [9].…”
Section: Discussionmentioning
confidence: 99%